Development and Evaluation of Management Information Systems for Christian Workers Movement Multi-Purpose Cooperative - M. Bernardo, Jose Carlos; E. Fidelino, John; A. Lamigo, Christian Noel; B. Santelices, Aaron Patrick; P. Ringula, Rex; G. Ventura, Mary Grace (International Journal of Informatics and Information Systems, 2018)
The Christian Workers Movement Multi-Purpose Cooperative (CWMMC) is a financial institution that caters to more than a thousand members in rendering timely financial assistance by making use of manual transaction processing. The company has encountered a number of problems pertaining to its services, strategic office location, and data / information management. This study was conducted in an attempt to design and develop a software system that would make loaning processes and other company-related business transactions simple, convenient, reliable, and dependable. A management information system was developed for and implemented at CWMMC. The software was found acceptable to the end-users and technical experts. Hence, it was recommended that the software be used continuously.